Respon Viabilitas Benih Kacang Tunggak Nagara (Vigna unguiculata ssp cylindrica) Akibat Pemberian Konsentrasi Ekstrak Akar Eceng Gondok (Eichhornia crassipes) - Raihani Wahdah; Hikma Ellya; Hasni Hairina (Rawa Sains: Jurnal Sains STIPER Amuntai, 2020)
Water hyacinth root contains Giberilin which was expected to improve the viability performance of nagara cowpea. The aim of this research was to study the effect of water hyacinth root extract on the viability of nagara cowpea. The research was carry out in April - October 2020 at the Plant Physiology Laboratory, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru. This research was arranged in a single factor completely randomized design, namely the concentration of water hyacinth root extract (control, 0%, 7.5%, 15.0%, 22.5%, and 30.0%). Observations were made on seed germination, viability potential, percentage of normal seedling at first observation, growth speed, uniformity of growth, root and plumule length of strong normal seedling, and dry weight of normal seedling.. If the treatment has a significant effect, then proceed with DMRT (Duncan Multiple Range Test). The 0.0% priming was better on all variables than the without priming, except for the root length. The 7.5% priming treatment was the most efficient for seed germination, potential germination of seeds, and growth uniformity of seeds. The 22.5% priming treatment was the most efficient for the germination percentage in first observation, seed growth speed, plumule length, and dry weight of normal seedling.